Associations among parent technology use, locus of control, and child problem behaviors. Issue 2 (16th December 2022) - Dworkin, Jodi; Sun, Xiaoran; LeBouef, Samantha; Keyzers, Angela
Abstract: Objective: The current study had two objectives: (a) describe demographic differences in parent technology use and (b) explore how parent technology use contributes to parent locus of control and how locus of control is associated with child problem behaviors. Background: The ubiquitous use of technology is likely to influence parenting and, in turn, children's outcomes. This study was designed to test the pathway from parents' technology use to children's problem behaviors through their locus of control for parenting. Method: Participants were 316 U.S. parents (36% fathers; M age  = 41.93 years), recruited through Amazon Mechanical Turk, with at least one child aged 10 to 18 years. Structural equation models were estimated to test the hypothesized paths. Results and Conclusion: Fathers and lower income parents reported significantly less frequent online information gathering and parents of color reported significantly more frequent calling and texting and social networking than White parents. Parents' texting and calling was positively, and online information gathering negatively, linked to child problem behaviors through parental locus of control. Implications: Understanding how diverse parents are using technology for parenting, and which online tools are effective for supporting parents is essential to developing online resources to support families.